Sifat Fisik dan Kimia Daging Landak Jawa (Hystrix javanica F. Cuvier, 1823) yang Diberi Tambahan Pakan Konsentrat - Farida, Wartika Rosa (Perhimpunan Biologi Indonesia, 2013)
This study is aimed to determine the effect of additional concentrate feed on the physical and chemical characteristicsof sunda porcupine meat. The material used is eight sunda porcupines (two males and six females) divided into twogroups of ration treatment, namely T0 (control ration) and T1 (T0 + koi fish pellets). Four porcupines (one maleand three females) were given control ration (T0) and four porcupines were given rations T1. The experimental designwas a completely randomized design. The meat physical characteristics measured were pH, tenderness, cookingloss, water holding capacity (WHC), meat color, and fat color. While meat chemical characteristics analyzed werewater content, ash, protein, fat, gross energy, calcium (Ca), phosphorus (P), iron (Fe), the content of fatty acids(EPA, DHA, Omega-3, Omega-6, Omega-9, and cholesterol), as well as the composition of amino acids. Data wereanalyzed by analysis of variance. The results showed no significant differences (P> 0.05) between male and femaleporcupine with both ration treatments (T0 and T1) on pH, tenderness, cooking loss, WHC, meat color, and fatcolor. The addition of koi fish pellets in the ration T1 decreased pH value (65.76) and cooking losses (37.88%), andincreased WHC porcupine meat (23.59%). Porcupine meat is quite tender with tenderness values of 3.63 kg / cm2(T0) and 3.26 kg / cm2 (T1). The averages of water content, ash, protein, fat, energy, Ca, P, Fe of porcupine meatwere not significantly different (P>0.05) in both treatments T0 and T1. The averages of fatty acids contents of porcupinemeat with T1 was not significantly different (P>0.01) from that of T0, but there was an increase in the concentrationof EPA, DHA, omega-3, omega-6, omega-9, and cholesterol in treatment of T1. Cholesterol content ofporcupine meat was lower than that of beef, pork, lamb, sambar deer, and java deer. No significant effect (P> 0.05)on content of amino acids in meat porcupine with T1 compared to that of T0.Keywords: Physical-chemical characteristics, meat, concentrate feed, sunda porcupine